Association of reperfusion success and emboli in new territories with long term mortality after mechanical thrombectomy. (28th April 2021) - Beyeler, Morin; Weber, Loris; Kurmann, Christoph C; Piechowiak, Eike Immo I; Mosimann, Pascal J; Zibold, Felix; Meinel, Thomas Raphael; Branca, Mattia; Goeldlin, Martina; Pilgram-Pastor, Sara M; Grunder, Lorenz; Arnold, Marcel; et al.
Abstract : Background: The degree of reperfusion is the most important modifiable predictor of 3 month functional outcome and mortality in ischemic stroke patients treated with mechanical thrombectomy. Whether the beneficial effect of reperfusion also leads to a reduction in long term mortality is unknown. Methods: Patients undergoing mechanical thrombectomy between January 2010 and December 2018 were included. The post-thrombectomy degree of reperfusion and emboli in new territories were core laboratory adjudicated. Reperfusion was evaluated according to the expanded Thrombolysis in Cerebral Infarction (eTICI) scale. Vital status was obtained from the Swiss population register. Adjusted hazard ratios (aHRs) using time split Cox regression models were calculated. Subgroup analyses were performed in patients with borderline indications. Results: Our study included 1264 patients (median follow-up per patient 2.5 years). Patients with successful reperfusion had longer survival times, attributable to a lower hazard of death within 0–90 days and for >90 days to 2 years (aHR 0.34, 95% CI 0.26 to 0.46; aHR 0.37, 95% CI 0.22 to 0.62). This association was homogeneous across all predefined subgroups (p for interaction >0.05). Among patients with successful reperfusion, a significant difference in the hazard of death was observed between eTICI2b50 and eTICI3 (aHR 0.51, 95% CI 0.33 to 0.79). Emboli in new territories were present in 5% of patients, and were associated with increased mortality (aHR 2.3, 95% CI 1.11 to 4.86). Conclusion: Successful, and ideally complete, reperfusion without emboli in new territories is associated with a reduction in long term mortality in patients treated with mechanical thrombectomy, and this was evident across several subgroups.